Economists and the financial markets - Brown, Brendan, 1951- (Routledge, 1996)
"This book explores how economists operate effectively in financial markets. Using events as diverse as the Wall Street Crash of 1929 to European monetary union and Japanese earthquake damage the author traces the responses of the market to a variety of financial events. In so doing, he shows how a knowledge of economics, correctly applied, can enhance investment performance." "This book is divided into sections dealing with a wide range of issues, including the valuing process; interpreting the news; the challenges of long-term business scenarios; the business and growth cycle; and the economist as strategist." "Throughout, the importance of scenario building is emphasized, along with illustrations of how the economist can build practical skills in the marketplace. Written in an accessible style, the book will be a valuable guide for students wishing to broaden their knowledge of economics away from the theoretical. It will also appeal to experienced market economists interested in a fellow professional's approach."--Jacket